Circadian variation of breakthrough pain in cancer patients. (19th June 2012) - Saini, A.; Tucci, M.; Tampellini, M.; Maina, D.; Bouraouia, K.; Giuliano, P.L.; Termine, A.; Castellano, M.; Campagna, S.; Laciura, P.; Berruti, A.
Abstract: Background: Breakthrough cancer pain (BTP) can place physical, psychological and economic burdens on patients and their productive life. By preventing instead of treating BTP after it occurs, the efficacy of analgesic treatment in cancer patients could be maximized. With this study, we investigated circadian variations in the occurrence of BTP events in cancer patients. Methods: The circadian variation of BTP was assessed in two different series (group 1, n  = 47; group 2, n  = 76) of advanced cancer patients suffering from severe chronic pain and undergoing analgesic treatment with major opioids. Results: BTP episodes showed a circadian pattern, with an acrophase occurring at 10:00 a.m. ( p  < 0.001) in all patients. When the two series of patients were considered separately, an acrophase was similarly observed, with 60% of BTP episodes recorded between 10:00 a.m. and 6:00 p.m. The circadian rhythm of BTP was maintained after stratifying the patients according to whether they had bone metastases or visceral metastases. BTP episodes negatively correlated with quality of life. Conclusions: BTP onset follows a circadian rhythm, with an acrophase occurring in the late morning.